Dampak Pengembangan Kurikulum Muatan Lokal Al-Islam Terhadap Kecakapan Pengetahuan Agama Islam Peserta Didik - Muh Irfhan Muktapa (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2022)
The impact of the development of the local content curriculum of al-Islam on the knowledge of the Islamic religion of students, the role of the curriculum as a forum in the development of Islamic religious learning becomes a method in producing students who have knowledge of the Islamic religion, so that they become students who always limit themselves in the corridor of religion. The problems are formulated as follows: 1. Knowing the Development of Al-Islam Local Content Curriculum at Miftahussa'adah Islamic High School. 2. Knowing the form of applying the Al-Islam local content curriculum to the Islamic religious knowledge skills of students at Miftahussa'adah Islamic High School. 3. Knowing the supporting and inhibiting factors for developing local content curriculum at SMA Islam Miftahussa'adah Parungkuda Sukabumi. To answer the above problems, the authors need to use Islamic education development research through analysis of primary or secondary data, interviews, observations and documents. The research specification is descriptive to describe what is done through qualitative means of theories regarding the development of Islamic education curriculum and the opinions of education experts. From the results of the study, it can be concluded that the impact of developing the local content curriculum of al-Islam is very good with the method of subject integrity making it easier for students to understand Islamic teachings in daily life. With this development the moral sector is growing among students by applying a smile and greeting in every daily activity.